2010
DOI: 10.4202/app.2009.1112
|View full text |Cite
|
Sign up to set email alerts
|

A New Fossil Provannid Gastropod from Miocene Hydrocarbon Seep Deposits, East Coast Basin, North Island, New Zealand

Abstract: Provanna marshalli sp. nov. is described from Early to Middle Miocene−age fossil hydrocarbon seep localities in the East Coast Basin, North Island, New Zealand, adding to 18 modern and three fossil species of the genus described. Modern species are well represented at hydrothermal vent sites as well as at hydrocarbon seeps and on other organic substrates in the deep sea, including sunken wood and whale falls. Described fossil Provanna species have been almost exclusively reported from hydrocarbon seep deposits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Kiel (2006) identified three microstructural layers in the shell of the fossil species P. antiqua Squires, 1995: an outer prismatic layer, a central complex crossed lamellar layer and an inner homogeneous layer. Given what we have seen in P. alexi this inner layer of P. antiqua might not be a primary structure, but could rather represent an innermost layer of dissolution and recrystallization, as suggested for P. marshalli by Saether et al (2010).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Kiel (2006) identified three microstructural layers in the shell of the fossil species P. antiqua Squires, 1995: an outer prismatic layer, a central complex crossed lamellar layer and an inner homogeneous layer. Given what we have seen in P. alexi this inner layer of P. antiqua might not be a primary structure, but could rather represent an innermost layer of dissolution and recrystallization, as suggested for P. marshalli by Saether et al (2010).…”
Section: Discussionmentioning
confidence: 88%
“…There is no inner prismatic layer in P. alexi, which is also the case for P. marshalli. Saether et al (2010) suggested that the lack of this layer in P. marshalli might have been due to differential taphonomic and diagenetic processes affecting the shells, either on the seafloor or during early burial, where the outer shell microstructural layers were protected for longer from these processes by the periostracum in relation to the innermost shell layers. An alternative explanation is that an inner layer of simple prismatic microstructure was not present in P. alexi and P. marshalli.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Kiel (2006) also re− ported a healed shell injury in a single specimen of Pro− vanna antiqua Squires, 1995 from the Oligocene Lincoln Creek Formation, north−western USA, that may have re− sulted from a predatory crab attack. Species of Provanna are often reported as endemic to vent−seep environments (e.g., Hessler and Lonsdale 1991;Warén and Bouchet 1993;Carney 1994;Yamamoto et al 1999;Fujikura et al 2002;Cordes et al 2009), but some species have been re− ported from other organic substrates such as sunken drift− wood Bouchet 2001, 2009) and whale falls (Smith et al 2002;Smith and Baco 2003). These more 508 ACTA PALAEONTOLOGICA POLONICA 55 (3), 2010 …”
Section: Introductionmentioning
confidence: 99%